Academic job satisfaction questionnaire: Construction and validation in Saudi Arabia - Abdullah M Al-Rubaish; Sheikh Idris A Rahim; Mahdi S Abumadini; Lade Wosornu (Wolters Kluwer Medknow Publications, 2011)
Background: Colleges and universities are becoming increasingly accountable for teaching outcomes in order to meet rigorous accreditation standards. Job satisfaction (JS) seems more difficult to measure in the academic field in view of the complexity of roles, duties and responsibilities. Objectives: To compile and determine the psychometric properties of a proposed Academic Job Satisfaction Questionnaire (AJSQ) suitable for university faculty, and amenable to future upgrading. Materials and Methods: A 46-item five-option Likert-type draft questionnaire on JS was distributed for anonymous self-reporting by all the academic staff of five colleges in University of Dammam (n=340). The outcome measures were (1) factor analysis of the questionnaire items, (2) intra-factor α-Coefficient of Internal Consistency Reliability, (3) inter-factor correlations, (4) comparison of psychometric properties in separately analyzed main faculty subgroups. Results: The response rate was 72.9 percent. Factor analysis extracted eight factors which conjointly explained 60.3 percent of the variance in JS. These factors, in descending order of eigenvalue, were labeled "Authority", "Supervision", "Policies and Facilities", "My Work Itself", "Interpersonal Relationships", "Commitment", "Salary" and "Workload". Cronbach's-α ranged from 0.90 in "Supervision" to 0.63 in "Salary" and "Workload". All inter-factor correlations were positive and significant, ranging from 0.65 to 0.23. The psychometric properties of the instrument in separately analyzed subgroups divided by sex, nationality, college and clinical duties produced fairly comparable findings. Conclusion: The AJSQ demonstrated good overall psychometric properties in terms of construct validity and internal consistency reliability in both the overall sample and its separately analyzed subgroups. Recommendation: To replicate these findings in larger multicenter samples of academic staff.